2015
DOI: 10.1039/c5py01293g
|View full text |Cite
|
Sign up to set email alerts
|

Improved control through a semi-batch process in RAFT-mediated polymerization utilizing relatively poor leaving groups

Abstract: The negative effect that a RAFT agent with a poor leaving group has on the evolution of molecular dispersity in a RAFT-mediated polymerization was shown to be mitigated by performing the polymerization in semi-batch mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
0
11
0
1
Order By: Relevance
“…On the other hand, for a too low [ R 0 X ] 0 : [ I 2 ] 0 a very fast RAFT polymerization results but the rate of RAFT deactivation becomes too low, leading to a chaotic monomer incorporation over the different polymer chains and ultimately to the loss of microstructural control. To reduce the reaction time and maintain well‐defined molecular properties the potential of semibatch conditions has been also investigated . For instance, Gody et al and Zetterlund et al have shown that by synthesizing shorter blocks with low amounts of I 2 a high livingness can be realized while having short reaction times for each block.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for a too low [ R 0 X ] 0 : [ I 2 ] 0 a very fast RAFT polymerization results but the rate of RAFT deactivation becomes too low, leading to a chaotic monomer incorporation over the different polymer chains and ultimately to the loss of microstructural control. To reduce the reaction time and maintain well‐defined molecular properties the potential of semibatch conditions has been also investigated . For instance, Gody et al and Zetterlund et al have shown that by synthesizing shorter blocks with low amounts of I 2 a high livingness can be realized while having short reaction times for each block.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the reaction time and maintain well-defined molecular properties the potential of semibatch conditions has been also investigated. [28,[30][31][32][33][34] For instance, Gody et al [30][31][32] and Zetterlund et al [33] have shown that by synthesizing shorter blocks with low amounts of I 2 a high livingness can be realized while having short reaction times for each block. Similarly, semibatch conditions were explored by Ilchev et al [34] to mitigate the effect of poor leaving groups by employing a low [M] 0 : [R 0 X] 0 and adding fresh monomer during the course of the polymerization.…”
mentioning
confidence: 99%
“…同时, 鉴于分批投料(semi-batch feeding)和连续 投料(continuous feeding)两类模式在工业生产中的应 用较为普遍 [133][134][135][136][137][138][139][140] , 我们拓展了有关成批投料模式下 的研究结果, 考察了分批投料和连续投料过程中的 投料方式、投料批次、投料数量及各反应阶段的转化 率等因素的影响. 为此, 引入了反应体系的生成函数 (generation function), 从而将各个反应的初始条件与 高分子的平均分子量和多分散指数等直接联系起来.…”
Section: 引言unclassified
“…These monomers typically contain a saturated carbon or an oxygen/nitrogen electron pair adjacent to the vinyl group, resulting in more reactive radicals with respect to RAFT addition (C tr(,0) > 10). 17,19,21,[24][25][26][27][28][29] Other more active RAFT agents such as dithioesters and trithiocarbonates (Fig. 1c) lead to the formation of INT radicals considerably more stable than the radicals formed by RAFT fragmentation, resulting in an undesired lowering of the polymerization rate.…”
Section: Introductionmentioning
confidence: 99%
“…For MADIX of MAMs, several kinetic studies have been performed with styrene as the monomer. 7,17,19,25,32,34,36,37 For example, Adamy et al 7 investigated the influence of the chemical structure of the initial RAFT agent for MADIX of styrene in toluene and reported that with (O-ethyl xanthate)-2-ethyl propionate (OEXEP) as the initial RAFT agent, a Đ close to 2 (X m = 20%) can merely be obtained. In contrast, by increasing the electron-withdrawing capacity of the Z group by incorporation of fluorinated groups at β-position to the oxygen atom, as for instance in (O-2,2,2-trifluoro ethyl xanthate)-2-ethyl propionate (OtFOX), a lower but still high Đ of 1.6 can be achieved (X m > 20%), in agreement with an earlier experimental study by Destarac et al 36 The latter observation was attributed to an increased reactivity of the SvC bond due to the decreased availability of the oxygen lone pair to conjugate with the thiocarbonyl group.…”
Section: Introductionmentioning
confidence: 99%